Leveraging Pharmacy Education through a Train-the-Trainer Model to Enhance Breast Cancer Literacy in Rural Communities - Christopher L. Farrell; Melanie R. Ginzburg; Morgan B. Enlow; Missouri M. Jenkins; Alexus N. Hames; Cayla R. Adams; Marlana A. Roberts; Hillary E. Stamps; Natalie A. Paxton; Courtney N. Addison; Austin Y. Shull (Journal of Cancer Education, 2026)
Rural versus urban communities experience disproportionate challenges in breast cancer outcomes, with higher breast cancer mortality and later stage disease presentation, despite similar diagnosis rates. These disparities are driven by structural barriers, including rural hospital closures, transportation difficulties, and limited access to oncology specialists. This study evaluated a train-the-trainer program designed to equip PharmD students located at a pharmacy school in a rural county in South Carolina with breast cancer education training, leveraging the pharmacists’ position as accessible healthcare professionals in rural communities. Training focused on breast cancer risk factors, prevention, screening, genetics, staging, and treatment options. Effectiveness was measured through pre- and post-workshop confidence surveys and knowledge assessments. Results showed significant improvement in student confidence across educational domains, with average scores increasing from 6.30 to 8.59 ( p < 0.0001). Understanding of screening guidelines (mean difference: 4.30; p -value: < .0001) and target therapy options showed the greatest improvement (mean difference: 3.65; p -value: < .0001), while knowledge of BRCA gene inheritance showed the smallest change (mean difference: 0.369; p -value: ns), suggesting some pre-existing awareness but limited understanding of its clinical applications. Overall, this pilot program demonstrates how pharmacy education can address healthcare disparities in rural communities. By preparing pharmacists to deliver accurate breast cancer education and to increase rural patient agency, this model creates a sustainable approach to improving health literacy in medically underserved areas. Future research could further expand this model to include diverse healthcare professionals and incorporate long-term impact assessments in community settings.

Assessment of CYP2D6 gene expression in liver tissue: Variability in CYP2D6 mRNA levels within genotype-predicted metabolizer phenotype groups - Erika L. Meaddough; Sara M. Sarasua; Deborah Kunkel; Luigi Boccuto; Satishkumar R. Ganakammal; Matt Moersen; Christopher L. Farrell (Chemico-Biological Interactions, 2025)

Temperature matters: Acute and latent toxicity of diluted bitumen to developing salmon is potentiated by a modest increase in water temperature - Derin M. Çalık; Feng Lin; Mackenzie Edgar; Anthony P. Farrell; Christopher J. Kennedy; Todd E. Gillis; Sarah L. Alderman (Aquatic Toxicology, 2025)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)